Impact of smoking status and smoking index on outcomes in patients with acute basilar artery occlusion - Han, Bin; Tong, Xu; Raynald; Jia, Baixue; Mo, Dapeng; Gao, Feng; Ma, Ning; Sun, Xuan; Miao, Zhongrong (Frontiers in Neurology, 2025)
PurposeThis study aims to investigate the relationship between smoking status, smoking index, and the outcomes of intravascular treatment for acute basilar artery occlusion within 24 h.MethodsWe retrospectively analyzed all consecutive patients hospitalized with acute basilar artery occlusion who underwent endovascular treatment within 24 h from January 2012 to July 2018 at Beijing Tiantan Hospital. Smoking status was categorized as never smoking, current smoking, or previous smoking. The smoking index (SI) was calculated as the daily smoking count multiplied by the number of smoking years. The primary outcomes were a 90-day modified Rankin Scale score shift analysis and mortality at 90 days.ResultsThe overall study cohort comprised 59 never smokers, 58 former smokers, and 70 current smokers. No significant differences in primary outcomes were observed between smoking status and functional independence (OR, 1.611; 95% CI, 0.776–3.344) or death (OR, 0.461; 95% CI, 0.196–1.084). Multivariate analysis indicated that smoking status had limited relevance to functional independence (OR, 1.958; 95% CI, 0.781–4.907) and death (OR, 0.446; 95% CI, 0.169–1.178). The smoking index was independently associated with functional independence (OR, 1.095; 95% CI, 1.015–1.182) and death (OR, 0.844; 95% CI, 0.757–0.941). The smoking index demonstrated a dose–effect relationship with outcomes, being positively correlated with functional independence and negatively correlated with death.ConclusionSmoking status does not appear to influence prognosis. However, the smoking index may be associated with improved functional independence and a reduced risk of death, demonstrating a dose-effect relationship.